FORUM: REFLEKSI AJEG BALI HARI INI - Gede Indra Pramana (Universitas Airlangga, 2013)
This paper traces the discourse on Ajeg Bali. As a formulation for the crisis in the post-boom Bali bombing in 2002, Ajeg Bali is considered as panacea that can solve all problems. By tracing the Ajeg Bali discourse and practices revealed in his name, found that amid the onslaught of the power of capital, mighty Ajeg Bali served as servant of power